INTERNATIONAL ASPECTS OF HUMAN TRAFFICKING – ESPECIALLY TRAFFICKING WITH MINORS - Ivanova, Elena (European Scientific Journal, ESJ, 2014)
Liberalization of understanding and relations, the liberation of sexuality from the constrains of primitivism and tradition, leads to rapid growth of prostitution as a socio-pathological phenomenon, which necessarily stimulate the emergence of crime - trafficking with human beings. Particularly worrying is the emergence of a new dimension of human trafficking - trafficking in minors. Children, in addition to women, in international documents, often receive the status of “specially protected persons” which, following the direction in which this crime is developing is more than justified. We can freely say that trafficking in minors is industry in development.